2002
DOI: 10.1021/ie011006f
|View full text |Cite
|
Sign up to set email alerts
|

Improved Autotuning Using the Shape Factor from Relay Feedback

Abstract: Since the introduction of the relay feedback test by Åström and Hä gglund (Automatica 1984, 20, 645-651), autotuning of PID controller has received much attention, and many commercial autotuners have also been designed accordingly. Without knowledge of the model structure, most of these relay feedback autotuners use Ziegler-Nichols-type tuning rules to set controller parameters. This can lead to poor performance in some cases, because no single tuning rule can work well for all model structures over the entir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(33 citation statements)
references
References 13 publications
0
33
0
Order By: Relevance
“…On the other side, deterministic performance assessment techniques consider more traditional design specifications such as those related to the set-point following and load disturbance rejection tasks [11]. In this context, different methods have been proposed for PI(D) controllers [12][13][14][15][16][17]. See [18] for a comprehensive description of all these techniques.…”
Section: Introductionmentioning
confidence: 99%
“…On the other side, deterministic performance assessment techniques consider more traditional design specifications such as those related to the set-point following and load disturbance rejection tasks [11]. In this context, different methods have been proposed for PI(D) controllers [12][13][14][15][16][17]. See [18] for a comprehensive description of all these techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The second method is the time required to reach the peak amplitude from the initial condition and is applicable only for the FOPDT process. [22] Chang et al . [21] have estimated time constants τ 1 and τ 2 using Eqns (3) and (4).…”
Section: Identification Of Linear Subsystemmentioning
confidence: 99%
“…Wang tion of a biased relay with hysteria to identify a first order plus dead time (FOPDT) model and revealed that the low order model can well approximate the high order processes [12]. Yu and co-worker studied the shape of the relay feedback response and derive the time constant of FOPDT model from time domain [13,14]. However, the early researches focused on chemical process control in which the nonlinear factors are not included.…”
Section: Introductionmentioning
confidence: 99%